TINGKAT PENGETAHUAN, PERSEPSI DAN SIKAP PASIEN TERHADAP KEHALALAN OBAT BATUK SIRUP DI APOTEK FARMARINDO BANYUMAS - Wijayanti, Rina; Mulya Prayoga, Deden; Priyatno, Sugeng (Sekolah Tinggi Ilmu Kesehatan Nasional & Pengurus Cabang Ikatan Apoteker Indonesia (IAI) Sukoharjo, 2024)
Medicine is one of the pharmaceutical products that has an important role in health. Medicine plays a role in reducing morbidity and mortality rates and improving a person's quality of life. Alcohol or khamr is one of the ingredients that is forbidden by Allah SWT. One medicine that contains alcohol is cough syrup. Many patients do not know whether cough syrup is halal. Therefore, this study aims to determine and measure the level of knowledge, perceptions, and attitudes of patients regarding the halalness of cough syrup containing alcohol at the Farmarindo Banyumas Pharmacy. This research is descriptive. Data collection was carried out using a questionnaire. Sampling used a purposive sampling technique with a total sample of 80 respondents. The results of the research show that the level of knowledge of respondents at the Farmarindo Banyumas Pharmacy regarding the halalness of cough syrup containing alcohol is 45% in the poor category, 10% in the sufficient category, and 45% in the good category. The level of perception of respondents at the Farmarindo Banyumas Pharmacy regarding the halalness of cough syrup containing alcohol is 79% in the good category and 21% in the very good category. The level of attitude of respondents at the Farmarindo Banyumas Pharmacy regarding the halalness of cough syrup containing alcohol is 74% in the good category and 26% in the very good category. It can be concluded that the level of knowledge, perceptions, and attitudes of respondents towards halal cough syrup medicine is in a good category.